Lipoprotein Signal Peptides Are Processed by Lsp and Eep of Streptococcus uberis - Denham, E. L. (American Society for Microbiology (ASM), 2008)
Lipoprotein signal peptidase (lsp) is responsible for cleaving the signal peptide sequence of lipoproteins in gram-positive bacteria. Investigation of the role of Lsp in Streptococcus uberis, a common cause of bovine mastitis, was undertaken using the lipoprotein MtuA (a protein essential for virulence) as a marker. The S. uberis lsp mutant phenotype displayed novel lipoprotein processing. Not only was full-length (uncleaved) MtuA detected by Western blotting, but during late log phase, a lower-molecular-weight derivative of MtuA was evident. Similar analysis of an S. uberis double mutant containing insertions disrupting both lsp and eep (a homologue of the Enterococcus faecalis “enhanced expression of pheromone” gene) indicated a role for eep in cleavage of lipoproteins in the absence of Lsp. Such a function may indicate a role for eep in maintenance of secretion pathways during disruption of normal lipoprotein processing.